ANALISIS KINERJA KEUANGAN PERUSAHAAN PT.INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK - Erny Setyowati; Sri Dwiningsih; Ike Ratnasari (RISTANSI: Riset Akuntansi, 2021)
Abstract It is important to assess the company's financial performance to assist management and investors in making decisions. One method to analyze the company's financial performance assessment is using the Economic Value Added (EVA) analysis method. EVA is an analytical method to determine the company's added value by subtracting economic profit from the cost of capital issued. EVA method analysis begins by calculating Net Operating Profit After Tax (NOPAT), Invest Capital (IC), Weighted Average Cost of Capital (WACC), Capital Charge (CC) and Economic Value Added (EVA). This study aims to assess the financial performance of PT. Sido Muncul's Herbal and Pharmaceutical Industry, 2017-2019 using the Economic Value Added (EVA) analysis method. This research is descriptive and uses a quantitative approach. The data in this study are financial statements, namely balance sheets and income statements. From the results of the study, the EVA value during the research year increased and was positive (EVA > 0). This shows that PT. The Herbal and Pharmaceutical Industry of Sido Muncul Tbk is able to create added economic value for management and investors (shareholders). After being compared with similar companies, the EVA value which occupies the highest position is PT. Kalbe Farma Tbk, then the next sequence is PT. Herbal and Pharmaceutical Industry Sido Muncul Tbk and the last one is PT Darya-Varia Laboratoria Tbk. Keywords: Financial statement analysis, NOPAT, IC, WACC, CC and EVA